Effects of surface treatment on the wettability and finishing properties of Acacia mangium Willd. wood - Mohammad Suffian James, Redzuan (2018)
Furniture manufacturers who are using Acacia mangium wood often experienced difficulties in getting high glossy and attractive finished surface. Such problem may be attributed to poor surface wettability as well as the anatomical structure of the wood itself. This study evaluates the effects of surface treatment on both the wettability and finishing properties of A. mangium wood. The A. mangium lumber was segregated into sapwood and heartwood prior to sanding. Two types of solvent, methanol (MeOH) and sodium hydroxide (NaOH), were used to treat the wood surface using different concentrations: 2%, 4%, 6%, 8%, 10%, 12% and, 14%. The treated surfaces were evaluated for surface roughness and contact angle according to ISO 4287 and ASTM D7334-08 respectively. The results show that untreated sapwood of A. mangium has significantly rougher surface compared to heartwood upon treatment with MeOH and NaOH, the surface roughness. NaOH-treated surface has relatively lower contact angle than MeOH-treated, and experienced a complete wetting within 4.2 s for sapwood and 6.8 s for heartwood. Nevertheless, the surface looks darker and the grain is less visible. Meanwhile, MeOH-treated surface took 6.4 s for sapwood and 15.1 s for heartwood to completely wet the wood surface but retained it’s original colour. Moreover, the wood grain was clearer and much enhanced. Based on both wettability and appearance, the best results were given by MeOH having 8% concentration. Evaluation on the effects of 8% MeOH pretreatment prior to coating was carried out for different coating systems i.e. nitrocellulose (NC), acid catalyst (AC) and polyurethane (PU). The coated surfaces were tested for adhesion test-cross cut, scratch resistance test, abrasion test, impact resistance test, surface roughness, and gloss measurements test according to the relevant standards. The results revealed that Acacia wood surface treated with 8% methanol resulted in superior finished surface compared to untreated panels except for gloss. Among the coating systems, AC and PU appears to be more compatible with MeOH compared to NC as shown by applying 8% methanol on the A. mangium surface prior to coating with AC or PU improved the quality of the finished A. mangium wood meeting the minimum requirements stipulated in the standards.